Drug‐Drug Interactions in Elderly Adults in Dentistry Care: a Cross-Sectional Study - Elham Abbaszadeh; Niloofar Ganjalikhan Hakemi; Maryam Rad; Molook Torabi (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: Given the increase in the population of the elderly patients and the risk of systemic diseases in these individuals, the prevalence of the intake of various drugs is higher in elderly patients, which exposes them to the side effects of drugs including potential drug-drug interactions (DDIs). Purpose: Therefore, the present study is an attempt to evaluate the drug interactions between the drugs used by the elderly patients visiting Kerman School of Dentistry and the common dental drugs in 2020. Materials and Method: This cross-sectional study was conducted on the elderly patients (≥60 years (who referred to Kerman School of Dentistry for dental problems. After obtaining the oral informed consent and collecting demographic information, the drugs used by the patients and their systemic diseases were questioned, listed, and compared with the drugs mentioned in their files. The drug interactions with the common dental drugs were studied in the elderly patients using the www.drugs.com website. Chi-square, T, ANOVA, Kruskal-Wallis, and Mann-Whitney tests were used to compare the variables. The significance level was 0.05. Results: Of participants included in this study, 78 (52%) were female and 72(48%) were male. The average age of these patients was 71.27 6.32 years. The most common systemic diseases were hypertension (57.3%), heart diseases (42.0%), and diabetes mellitus (40.7%). Our analysis of the DDIs between 11 commonly prescribed dental drugs and 95 drugs used by the patients revealed 212 DDIs (21.7% minor, 68.3% moderate, and 9.9% major interactions). There was a significant relationship between the number of drugs and DDIs, whereas DDIs had no significant relationship with gender and educational level. Conclusion: The results reflected the high percentage of DDIs among the patients. In addition, there was a significant relationship between polypharmacy, which is highly prevalent among the elderly patients, and drug interactions.